Consumer behaviour and social network sites : the impact of negative word of mouth - Zaraket, Sarah (Oxon: Routledge, 2021)
"This book provides a solid understanding of electronic word of mouth (eWOM) by taking the reader through the process of information diffusion from rumour generation in times of traditional word of mouth (WOM) to negative social eWOM and examining how consumers process it. Consumer Behaviour and Social Networks tackles different themes relating to negative eWOM. Drawing on both intensive scientific research and professional examples, it bridges the gap between the academic and professional worlds. The book contrasts negative social eWOM to traditional WOM while discussing the specificities of different social networking sites in diffusing such information. It looks at why and how consumers decide to create, share and react to negative social eWOM, suggesting that there are more reasons than are commonly presumed for consumers to articulate themselves on these platforms. It also provides an appreciation of Millennial behaviours with regards to negative social eWOM and how it can alter their decision-making journey. The book concludes with several strategies and key takeaways to deal with and prevent negative social eWOM, while also presenting case studies of brands that have already dealt with it. Most books on WOM are purely professional and lack the theoretical contextualization of the issue. Moreover, they often provide insights on brand-to-consumer conversation but not consumer-to-consumer (C2C) communication. This short book provides marketing academics, students and practitioners with an important insight into these C2C communications that can potentially be harmful to brands"--
Once upon a word... -- ... social media amplified the voice for WOM -- People started talking negatively about brands on SNS... -- ... this impacted other consumer's reactions -- So how can you deal with NSWOM?
Includes bibliographical references and index.
Keywords: Consumer behavior; Social media; Online social networks; Word-of-mouth advertising; Consumer complaints